These were the Greeks - Amos, H. D. (Hugh Desmond), 1933-; Lang, A. G. P. (Andrew George Paul), 1939- (Amersham, Bucks. : Hulton Educational Publications ; [Chester Springs, Pa.] : Distributed in U.S.A. by Dufour Editions, 1979)
Discusses the land, history, government, economy, culture, and people of ancient Greece.
"Companion volume to These were the Romans, by C.I.F. Tingay and J. Badcock"--Pref.
Distribution statement stamped on t.p.
Includes index.
Bibliography: p. 222-223.
Keywords: Greece -- Civilization -- To 146 B.C.